Kelayakan Usahatani Padi Inpari IR Nutri Zinc Kelompok Tani Ngudi Makmur Kabupaten Tulungagung - Siti Chumidah; Andajani, Wiwiek; Sidhi, Eko Yuliarsha; Agustia Dwi Pamujiati (Jurnal Ilmiah Pertanian Nasional, 2024)
Tulungagung Regency ranks 18th with 2,901 stunting cases, the equivalent of 5.51% in East Java. More specifically, stunting cases in Kauman District, Tulungagung Regency, reached 104 or around 3.6%. One of the causes of stunting is iron (Zn) deficiency. The Tulungagung Regency Agriculture Service conducted an Inpari IR Nutri Zinc Rice cultivation development program for the Ngudi Makmur Farmers Group in Balerejo Village, Kauman District, to support reducing stunting cases. Cultivating Inpari IR Nutri Zinc Rice has been carried out well. However, an analysis of the costs and feasibility of farming has yet to be carried out, so further research needs to be conducted. This research aims to determine the costs and feasibility of cultivating Inpari IR Nutri Zinc Rice. This research was a quantitative descriptive study involving the participation of 30 respondents belonging to the Ngudi Makmur Farmers Group, Balerejo Village, Kauman District, determined by census. Cost analysis calculations included variable and fixed costs so that income and receipts would be known. Feasibility analysis was calculated using the R/C ratio. The study findings showed that the average expenditure figure for Inpari IR Nutri Zinc Rice agricultural activities in the Ngudi Makmur Farmer Group was IDR10,382,373 with an income of IDR19,463,007 per ha in one planting season. The R/C ratio calculation result was 2.88. This shows that the Inpari IR Nutri Zinc Rice cultivation business is profitable and feasible. Kabupaten Tulungagung menempati urutan ke-18 dengan jumlah 2901 kasus stunting atau setara dengan 5,51% di Jawa Timur. Lebih spesifik lagi, kasus stunting di Kecamatan Kauman Kabupaten Tulungagung mencapai 104 atau sekitar 3,6%. Salah satu penyebab stunting yaitu kekurangan zat besi (Zn). Dinas Pertanian Kabupaten Tulungagung melakukan program pembinaan budidaya Padi Inpari IR Nutri Zinc kepada Kelompok Tani Ngudi Makmur Desa Balerejo Kecamatan Kauman untuk mendukung penurunan kasus stunting. Proses budidaya Padi Inpari IR Nutri Zinc telah dilakukan dengan baik, namun belum dilakukan analisis biaya serta kelayakan usahataninya sehingga perlu dilakukan penelitian lebih lanjut. Tujuan penelitian ini untuk mengetahui biaya dan kelayakan usaha budidaya Padi Inpari IR Nutri Zinc. Penelitian ini adalah suatu studi deskriptif kuantitatif yang melibatkan partisipasi dari 30 responden anggota Kelompok Tani Ngudi Makmur Desa Balerejo Kecamatan Kauman yang ditentukan secara sensus. Penghitungan analisis biaya meliputi biaya variabel dan biaya tetapsehingga akan diketahui pendapatan dan penerimaan. Analisis kelayakan dihitung menggunakan R/C ratio. Temuan studi menunjukkan angka rata-rata pengeluaran dalam kegiatan pertanian Padi Inpari IR Nutri Zinc pada Kelompok Tani Ngudi Makmur sebesar Rp10.382.373 dengan pendapatan sebesar Rp 19.463.007 per ha dalam satu musim tanam. Hasil perhitungan R/C ratio sebesar 2,88. Hal ini menunjukkan bahwa usahatani budidaya Padi Inpari IR Nutri Zinc menguntungkan dan layak untuk dijalankan.